Sustained Preoperative Opioid Use Is a Predictor of Continued Use Following Spine Surgery. (6th June 2018) - Schoenfeld, Andrew J.; Belmont, Philip J.; Blucher, Justin A.; Jiang, Wei; Chaudhary, Muhammad Ali; Koehlmoos, Tracey; Kang, James D.; Haider, Adil H.
Abstract : Background: Preoperative opioid use is known to increase the likelihood of complications and inferior outcomes following spine surgery. We evaluated the association of preoperative opioid use and other risk factors with postoperative opioid use. Methods: We queried 2006-2014 TRICARE insurance claims to identify adults who underwent lumbar interbody arthrodesis, lumbar discectomy, lumbar decompression, or lumbar posterolateral arthrodesis. The duration of preoperative opioid use was categorized as acute exposure, exposed without sustained use, intermediate sustained use, and chronic sustained use. Cox proportional-hazard models that adjusted for demographic factors, preoperative diagnoses, comorbidities, postoperative complications, and the type of procedure performed were used to identify factors associated with a reduced likelihood of opioid discontinuation following the surgical procedure. Results: There were 27, 031 patients included in this analysis. Following the surgical procedure, 67.1% of patients had discontinued opioid use by 30 days, and 86.4% had ceased use by 90 days. Overall, 2, 379 patients (8.8%) continued to use opioid medications at 6 months. Duration of preoperative opioid use, among other demographic and clinical factors, was the most important predictor of continued use following a surgical procedure. Conclusions: The majority of patients who were using prescription opioids prior to the surgical procedure discontinued these medications postoperatively. Duration of preoperative use appears to be the most important predictor of sustained use following a surgical procedure. Clinical Relevance: Our results indicate that the majority of patients who are using prescription opioids prior to spine surgery discontinue these medications following surgical intervention. Among those who continue opioid use ≥90 days after the surgical procedure, the duration of preoperative use appears to be the most important predictor.